Lateral characteristics of rigid piles under large displacement. (January 2019) - Hu, Haibo; Feng, Zhongju; Zhao, Yawan; Feng, Kai; Jiang, Guan; Dong, Yunxiu; Wu, Min; He, Jingbin
Abstract: Based on the model test data and the numerical simulation method, the characteristics of rigid piles under large displacement are studied in this paper. The results show that the bending moment of the pile has a linear growth in the cantilever segment, when the distance from the top of the pile is greater than 0.7m, the increasing trend of the pile's bending moment gradually slows down, the bending moment of the pile becomes the maximum when the distance from the top of the pile is 1.1m, and the bending moment tending to 0 near the bottom of pile. In the case of large displacement, the soil in front of the pile shows obvious plastic yielding, and the soil resistance of the pile is no longer linearly increased with the increase of load.